Associations between statins and adverse events in secondary prevention of cardiovascular disease: Pairwise, network, and dose-response meta-analyses of 47 randomized controlled trials - Wang, Xinyi; Li, Jingen; Wang, Tongxin; Zhang, Zihao; Li, Qiuyi; Ma, Dan; Chen, Zhuo; Ju, Jianqing; Xu, Hao; Chen, Keji (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To explore the associations between different types and doses of statins and adverse events in secondary prevention of cardiovascular disease. Methods: We searched PubMed, Embase, and Cochrane databases for randomised controlled trials that compared statins with non-statin controls or different types or doses of statins. The primary outcomes included muscle condition, transaminase elevations, renal insufficiency, gastrointestinal discomfort, cancer, new onset or exacerbation of diabetes, cognitive impairment, and eye condition. We also analyzed myocardial infarction (MI), stroke, death from cardiovascular diseases (CVD), and all-cause death as the secondary outcomes to compare the potential harms with the benefits of statins. We conducted pairwise meta-analyses to calculate the odds ratio (OR) and 95% confidence intervals (CIs) for each outcome. Network meta-analyses were performed to compare the adverse effects of different statins. An Emax model was used to examine the dose-response relationships of the adverse effects of each statin. Results: Forty-seven trials involving 107,752 participants were enrolled and followed up for 4.05 years. Compared with non-statin control, statins were associated with an increased risk of transaminase elevations (OR 1.62 [95% CI 1.20 to 2.18]). Statins decreased the risk of MI (OR 0.66 [95% CI 0.61 to 0.71], P<0.001), stroke (OR 0.78 [95% CI 0.72 to 0.84], P<0.001), death from CVD (OR 0.77 [95% CI 0.72 to 0.83], P<0.001) and all-cause death (OR 0.83 [95% CI 0.79 to 0.88], P<0.001). Atorvastatin showed a higher risk of transaminase elevations than non-statin control (OR 4.0 [95% CI 2.2 to 7.6]), pravastatin (OR 3.49 [95% CI 1.77 to 6.92]) and simvastatin (OR 2.77 [95% CI 1.31 to 5.09]), respectively. Compared with atorvastatin, simvastatin was associated with a lower risk of muscle problems (OR 0.70 [95% CI 0.55 to 0.90]), while rosuvastatin showed a higher risk (OR 1.75 [95% CI 1.17 to 2.61]). An Emax dose-response relationship was identified for the effect of atorvastatin on transaminase elevations. Conclusions: Statins were associated with increased risks of transaminases elevations in secondary prevention. Our study provides the ranking probabilities of statins that can help clinicians make optimal decisions when there is not enough literature to refer to.